Enkätundersökning hos markägare inom SCA Skog Ångermanlands Skogsförvaltning - Berg, Christoffer (SLU/School for Forest Management, 2011)
This report is a joint venture with SCA Forest, Ångermanlands forest man-agement area. The purpose of the study is that SCA Forest wants to know what the landowners in Ångermanlands forest management area think about SCA Forest and who they deliver their timber to. SCA Forest is the largest private landowner in Europe, with an area of about 2.6 million hectares. Today, SCA offers lumber, wood products, tis-sue and packaging and has factories all over the world. SCA Forest has five forest management areas in the north of Sweden, with the headquarters in Sundsvall. A questionnaire was sent to 265 landowners, where they had to answer 15 questions with possibilities to give comments. The survey was sent out on 21 of February with a response requested by 3 of March 125 landowners responded to the survey, giving a response rate of 47%. Of the 125 landowners who responded were 86 men, 34 women and 5 which did not specified gender. Most of the landowners that had SCA Forest as their partner regarding for-est management tasks were satisfied with the outcome.